Morphofunctional peculiarities, methods of examination, semiotics of affection blood system in children : methodical recommendations for students of 3 course of medical faculty - Pavlova, O. S.; Rzhevska, O. O.; Павлова, Ольга Сергіївна; Ржевська, Ольга Олександрівна (Kharkiv : V. N. Karazin Kharkiv national university, 2021)
Methodical recommendation is worked out on the basis of the Program of discipline «Propaedeutics of pediatrics» for students of higher medical educational institutions of ІІІ–ІV levels of accreditation, authorized by Ministry of Health of Ukraine. This recommendation is intended for English-speaking medical students of the 3rd year.

Методичні рекомендації розроблено на основі Програми дисципліни «Пропедевтика педіатрії» для студентів вищих медичних навчальних закладів ІІІ–ІV рівнів акредитації, затвердженої МОЗ України. Ця рекомендація призначена для англомовних студентів-медиків 3 курсу.
Морфофункціональні особливості, методи дослідження, семіотика ураження системи крові у дітей : методичні рекомендації для студентів 3 курсу медичного факультету
Навчальне видання
Keywords: MEDICINE; SOCIAL SCIENCES; blood system; lymphatic system; methodology of the study of the blood system; кровоносна система; лімфатична система; методика дослідження системи крові